Incremental comprehension of pitch relationships in written music: Evidence from eye movements. Issue 1 (January 2018) - Hadley, Lauren V; Sturt, Patrick; Eerola, Tuomas; Pickering, Martin J
To investigate how proficient pianists comprehend pitch relationships in written music when they first encounter it, we conducted two experiments in which proficient pianists' eyes were tracked while they read and played single-line melodies. In Experiment 1, participants played at their own speed; in Experiment 2, they played with an external metronome. The melodies were either congruent or anomalous, with the anomaly involving one bar being shifted in pitch to alter the implied harmonic structure (e.g. non-resolution of a dominant). In both experiments, anomaly led to rapid disruption in participants' eye movements in terms of regressions from the target bar, indicating that pianists process written pitch relationships online. This is particularly striking because in musical sight-reading, eye movement behaviour is constrained by the concurrent performance. Both experiments also showed that anomaly induced pupil dilation. Together, these results indicate that proficient pianists rapidly integrate the music that they read into the prior context and that anomalies in terms of pitch relationships lead to processing difficulty. These findings parallel those of text reading, suggesting that structural processing involves similar constraints across domains.